Gross total resection of intracisternal accessory nerve schwannomas using a familiar midline suboccipital subtonsilar approach. Issue 7 (11th July 2019) - Antoniades, Elias; Athanasiou, Alkinoos; Sarlis, Panagiotis; Magras, Ioannis; Patsalas, Ioannis
Abstract: Background: Intracisternal Accessory Nerve Schwannomas (ANS) constitute a rare clinical entity with only a few cases reported so far. Their symptoms are usually due to brainstem compression and not manifested until they render of great size. Secondary neuropathy and muscle atrophy are other late signs. The hitherto reported literature advocates a suboccipital craniotomy as a suitable approach. In most of the cases the spinal root was the location tumor arose from. Gross total resection was possible to be carried out in most cases with only sporadic tolerable postoperative deficits reported. Case description: We hereby present three cases of patients with intracisternal ANS treated in the same fashion. Two patients were male and one female. Two patients complained of mainly chronic headaches and neck pain, whereas in the third patient the lesion was found incidentally. Only one patient suffered post-operatively cerebrospinal fluid leakage and wound healing complication, which was treated with revision surgery and administration of antibiotics. None of the patients had postoperative neurological deficits. Furthermore, we conducted a review of the relevant literature where we noted that there is no consensus yet with regards to the appropriate surgical approach. Conclusions: Based on relevant anatomical studies, we advocate that suboccipital subtonsilar approach provides a wide corridor to the area of lesion allowing complete and safe resection of intracisternal ANS. We thus support that, in most cases, the neurosurgeon should consider using this familiar approach for treating this rare lesion.